Azyumardi Azra's Islamic Education Thoughts - NUR RIDWAN; Sutomo Sutomo (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2021)
Education's primary objective is to develop pupils who comprehend and apply Islamic sciences in daily life. In other words, the realization of human beings, namely people who reconnect with their nature and the goal of their lives, as he pledged to be a human who came from Allah and would return to Allah. Azyumardi Azra's opinions on Islamic education are the product of his efforts to improve the quality of Islam's education. The issue at hand is the aim and curriculum of Islamic education. Regarding Azyumardi Azra's views on Islamic education, he emphasizes the importance of democratizing and modernizing Islamic education in order to elevate the dignity of Islamic educational institutions that generate high-quality education. Azyumardi Azra focuses on the intake and output of Islamic education for society when it comes to updating. By fusing traditional and forward-thinking ideals.